(3eaGJjM GdQMeI (B((3aj GdcjejGA(B)s - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s ((3LGO Hf eMeO Hf MSjf GdWgQGfi GdedbH HfLe GdedI s)
(3ChdgG (B:s
(3hHYO abO LGdSJ MbGFb SQ JOHjQ Gdbhe ai Ref dG jGNP ajg SQ jbXI Gdfhe s
(3BNQgG (B:s
(3bO Je GdLRA GdChd GdeSei HeaGJjM GdQMeI hjJdhg GdLRA GdKGfi hgh GdeSei HLGeY GdCSQGQ GdMcje GdaGVd eDjO GdOjf GdTgjO GdWZQGFi s
(3hQO Ydi GdfSNI GSe GdeDda GdeLQjWi abWs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B198 s
Keywords: (3GdcjejGA h GdWHjYjGJs